2021
DOI: 10.1371/journal.pone.0260841
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 E1 dysregulated cellular genes involved in cell proliferation and host DNA damage: A possible role in cervical carcinogenesis

Abstract: HPV16 is the most prominent cause of cervical cancer. HPV16 E1, a helicase required for HPV replication exhibits increased expression in association with cervical cancer progression, suggesting that E1 has a similar effect on the host as the HPV16 E6 and E7 oncoproteins. This study aimed to determine whether expression of HPV16 E1 correlated with carcinogenesis by modulating cellular pathways involved in cervical cancer. HEK293T cells were transfected with pEGFP, pEGFPE1 or truncated forms of HPV16 E1. Cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…CREB5 is a member of the CRE-BP1 family of the cAMP response element-binding proteins [34,35]. To date, studies on the role of CREB5 in tumors have mainly focused on invasion, metastasis, and proliferation [12,16,[36][37][38][39][40]. In addition, it has been reported that CREB5 expression can negatively regulate HBV and human enterovirus-a71 (EV-a71) replication [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…CREB5 is a member of the CRE-BP1 family of the cAMP response element-binding proteins [34,35]. To date, studies on the role of CREB5 in tumors have mainly focused on invasion, metastasis, and proliferation [12,16,[36][37][38][39][40]. In addition, it has been reported that CREB5 expression can negatively regulate HBV and human enterovirus-a71 (EV-a71) replication [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…More functional assays related to the hallmarks of cancer, e.g., cell proliferation, apoptosis, cell cycle arrested, migration/invasion, wound healing, and colony formation, should be done in E1 overexpressed/knockdown/knockout cells. Moreover, many genes such as BCL2L1, CSP2, FOXO3a, JMJDIC, and TSC22D3, were dysregulated in either HPV18 or HPV16 E1 overexpressed/knockdown cells ( Castillo et al., 2014 ; Baedyananda et al., 2021 ). To better understand the E1 associated cellular pathways, the relationship between E1 and those genes as well as E1 protein-protein interaction should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to induce apoptosis could drive tumorigenesis through multiple mechanisms ( Ichim and Tait, 2016 ). In HPV16 E1 overexpressing cells, several host genes that are involved in protein synthesis (RPL36A), metabolism (ALDOC), immune response (ISG20), DNA damage (ATR, BRCA1, and CHK1), and cell proliferation (CREB5, HIF1A, NFKB1, PIK3CA, JMJDIC, TSC22D3, FOXO3), have been shown to be significantly downregulated ( Baedyananda et al., 2021 ). Of the transcriptional factors, CREB5, HIF1A, NFKB1, and PIK3CA, downregulation of NFKB1 and PIK3CA supports tumor growth and survival ( Xia et al., 2014 ; Masoud and Li, 2015 ).…”
Section: The Possible Functions Of Hpv16 E1 In Cervical Carcinogenesismentioning
confidence: 99%
“…Gao et al reported that GMNN can be used as a diagnostic marker in liver cancer [34]. TSC22D3 is not only associated with tumors [35], but TSC22D3 mRNA expression is signi cantly downregulated in liver biopsy samples from patients with hepatic brosis and is negatively correlated with CCL2 expression [36]. However, the correlation of these genes with osteogenic differentiation is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…TSC22D3 is highly expressed during T-cell transition and is highly correlated with the clinical staging of the tumor [38]. Further, TSC22D3 has been implicated in the cell-proliferation signaling system in the bioinformatics analysis of cervical cancer-related genes, and is related to cervical cancer incidence [35]. TSC22D3 is also involved in various response processes as a glucocorticoid receptor gene [39].…”
Section: Discussionmentioning
confidence: 99%